2020
DOI: 10.1186/s12934-020-01436-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis: a universal cell factory for industry, agriculture, biomaterials and medicine

Abstract: Due to its clear inherited backgrounds as well as simple and diverse genetic manipulation systems, Bacillus subtilis is the key Gram-positive model bacterium for studies on physiology and metabolism. Furthermore, due to its highly efficient protein secretion system and adaptable metabolism, it has been widely used as a cell factory for microbial production of chemicals, enzymes, and antimicrobial materials for industry, agriculture, and medicine. In this mini-review, we first summarize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
176
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(184 citation statements)
references
References 102 publications
2
176
0
6
Order By: Relevance
“…We examined an amino acid sequence alignment of Vip3Aa sequences from different Bt strains (Estruch et al ., 1996; Doss et al ., 2002); however, we could not detect signal peptides in these sequences using the SignalP 5.0 server. Some studies have shown that proteins lacking any known signal peptides or secretion motifs are secreted via several non‐classical pathways (Zhao et al ., 2017; Su et al ., 2020). For instance, an autolytic enzyme lacking signal peptides can be transported to the cell wall of B. subtilis (Potvin et al ., 1988; Kuroda and Sekiguchi, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…We examined an amino acid sequence alignment of Vip3Aa sequences from different Bt strains (Estruch et al ., 1996; Doss et al ., 2002); however, we could not detect signal peptides in these sequences using the SignalP 5.0 server. Some studies have shown that proteins lacking any known signal peptides or secretion motifs are secreted via several non‐classical pathways (Zhao et al ., 2017; Su et al ., 2020). For instance, an autolytic enzyme lacking signal peptides can be transported to the cell wall of B. subtilis (Potvin et al ., 1988; Kuroda and Sekiguchi, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…No significant antibacterial activity was detected from the NRRL3_00042 OE extract. The Gram-positive B. subtilis has been studied for its probiotic properties and is a major industrial host for protein production [ 31 ]. B. subtilis can grow in co-culture with A. niger and it resulted in a down-regulation of this BGC [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several members of the genus Bacillus (e.g., Bacillus subtilis , Bacillus licheniformis , and Bacillus megaterium ) are used as industrial cell factories for the manufacturing of bulk and fine chemicals and proteins of biotechnologically interest ( Schallmey et al, 2004 ; Korneli et al, 2013 ; Van Dijl and Hecker, 2013 ; Su et al, 2020 ). There is an increasing demand for environmentally friendly and sustainable microbiologically based biotechnological processes that do not compete with the use of human or animal food-stocks.…”
Section: Introductionmentioning
confidence: 99%